Non-Profit Social Purpose and Social Enterprise Outcome Themes That Transfer to Businesses - Mendel, Stuart C. (American Journal of Management, 2022)
The attention cast toward social enterprise since the mid to late 1990s by private businesses, nonprofit human service organizations, and public sector stakeholders has driven interest in the best ways to measure social mission-related outcomes and whether or not such endeavors truly achieve impactful change. Little clarity from the methodological models has emerged to inform social mission outcome measurement due in part to the blurring of cross-sector principles underlying the tasks at hand. A barrier is that businesses engaged in social mission must make choices that redefine profit-making, and it is a rare case where nonprofit and social purpose organization (SPO) evaluation models trace whether or not and to what degree their efforts have led to the social outcomes they profess to accomplish. This essay depicts the compromises and accommodations leaders and decision makers among five case examples encompassing philanthropic, nonprofit human services and social service providers, government and business actors make in their social enterprise work toward social mission outcomes and impact.